Elección de un comportamiento urbano responsable a partir del beneficio, la saliencia del anuncio y la probabilidad de recibir aprobación y reproche (2021)
Through a correlational study, this research explores the influence of possible social benefits and associated variables over the adoption of Responsible Urban Behaviors (RUB). Taking into account the complexity of the problem and the number of variables to be explored, the model of Facet Theory was used. Also, a questionnaire was created, which shows hypothetical urban situations in the form of vignettes that explore the variables under study. 177 participants estimated the probability of an individual involved in a vignette adopting a RUB or not, based on the temporal distance and magnitude of the benefit, the salience of the announcement of such benefit, and the social approval and reproach. A Smallest Space Analysis (SSA) showed that participants recognize these variables in mind when it comes to opting for a RUB. The temporal distance to obtain the benefit and the large magnitude of the benefit turned out to be highly correlated with the highest estimation of the probability of an individual choosing a RUB. This research suggests to formulate educational strategies and public policies that lead to the development of cooperation, responsibility, and self-regulation, to help improve the quality of urban life and conviviality in the urban environment.